STIMMAP : Nova metodologia para monitoramento de fraturas em poços produtores - OLIVEIRA, Larissa Beatriz Reis (2019)
The present Course Final Report (TCC) has as objective to address a new methodology for monitoring the process of stimulation of producing wells by hydraulic fracturing, and is in the internship project funded by the Schlumberger Company, held in July 2008. The project aims to identify and orient fractures generated by the process of stimulation through the capture of microseismic events generated by the large release of energy produced by the billing, to improve production and management of producing wells in the region of Carmópolis in the state of Aracaju. This work is basically divided into 3 steps: (1) View wide on the processes of stimulation and producing wells and their features, the sonic log presentation and their importance to the work and finally, notions and principles of the VSP (Vertical Seismic Profile), which also has a stake in the landmark, (2) Geology of the region of Carmópolis and characteristics and details of the stages of data acquisition, (3) Presentation of results. Overall, we achieved 4 stages of fracture, in which only two of these stages are presented in this work due to issues of Petrobras confidentiality, owner of the wells where was done the job.